A new species of the genus Smithophis (Squamata: Serpentes: Natricidae) from southwestern China and northeastern Myanmar - Vogel, Gernot; Chen, Zening; Deepak, V.; Gower, David J.; Shi, Jingsong; Ding, Li; Hou, Mian (Zootaxa, 2020)
A new species of natricid snake, Smithophis linearis sp. nov., is described on the basis of a single recently collected specimen from Yingjiang County, Yunnan Province, People’s Republic of China, and three historical specimens from Yunnan and from northeastern Myanmar. The new species is assigned to the genus Smithophis on the basis of its single internasal and single prefrontal shields, and on the basis of the results of phylogenetic analysis of mitochondrial cytochrome b DNA sequence data. The new species differs from its congeners in having the following combination of characters: temporal shields present, six or more circumorbital scales, and a distinctive colour pattern comprising regular, narrow, longitudinal dark and pale lines. Morphological and cytochrome b data are consistent with the recognition of Smithophis as distinct from the genus Opisthotropis. A revised key to the identification of the species of Smithophis is provided.